Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Mousson de femmes - Perrin, Elula (La Cerisaie, 2003)
Récit d'un amour passionné entre deux femmes en Indochine pendant la Seconde Guerre mondiale. Elula Perrin, née à Hanoi en 1929, témoigne de la terreur et des tueries perpétrées en Indochine entre 1945 et 1946.
Keywords: 1900-1999; 1940-1949; approches et analyses; asie; guerre; mémoire collective; personnes lesbiennes; périodes historiques; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; violences